The impact of the SWOM strategy on the acquisition of grammatical concepts among students of Colleges of Education- University of Tikrit and Developing Their Critical Thinking - al-Jubouri, Falah (Journal of Tikrit university for humanities - مجلة جامعة تكريت للعلوم الانسانية, 2019)
The researcher used the experimental design which consists of two groups; target and control. The researcher chose the colleges of education at the University of Tikrit. In my opinion, the College of Education for Humanities should be chosen as a target group to study the use of this strategy. A number of variables are thought to affect the experiment.  The researcher identified the educational material to be taught, which is the book of Ibn Aqil. The researcher also prepared model teaching plans for both group. The research tool was the test of the acquisition of grammatical concepts, which included (33) items that measure the three processes of acquisition of the concept, and verified its validity, reliability, discriminating power, the effectiveness of the wrong alternatives and its difficulty coefficient. The second tool was a test of critical thinking, After the experiment was completed, the researcher applied the research tools (the test of the acquisition of the post-grammatical and post-critical thinking) to the two research groups. After collecting and processing the data using the independent two-1 There is a statistically significant difference at (0.05) between the average grade of the target group that is studying the grammatical material according to the same strategy and the test of acquisition of the grammatical concept and for the benefit of the target group.